Sailing - LaCrosse, Michelle, author (Colorado State University. Libraries, 2017)
This essay examines the narrator's desire to travel and explore, what that means to her family life, and how she feels about it through personal experiences with sailing, growing up in the Pacific Northwest and learning about the lives and journeys of early global explorers.
Michelle E. Lacrosse
Excerpt thesis reading - Sailing
Keywords: creative nonfiction; sailing; personal narrative; essay